0039 Circadian Variation of Plasma Triglycerides in Healthy Adults. (12th April 2019) - Yuan, Robin K; Zitting, Kirsi-Marja; Vujovic, Nina; Wang, Wei; Buxton, Orfeu M; Williams, Jonathan; Czeisler, Charles A; Duffy, Jeanne F
Abstract: Introduction: The lipid panel is a commonly ordered laboratory test used to determine cardiovascular disease event risk. Although numerous plasma lipids exhibit diurnal variations, clinical instructions for the lipid panel typically do not specify a time of day for testing. We used a forced desynchrony (FD) protocol to examine whether the lipids in the fasting lipid panel vary with circadian phase in healthy adults. Methods: Six healthy adults (38-69 years; 3f) participated in a 37-day inpatient protocol with a regular (25-27% fat) or high-fat diet (45-50% fat). Three participants completed the study twice, once in each diet condition. Subjects' rest-activity 3 of the study weeks were scheduled on 28-hour FD "days" with 11.67-h sleep opportunities. Fasting blood samples were collected <2 hours after wake time, and assayed for cholesterol, triglycerides, HDL, LDL, and VLDL (LabCorp). Continuous core body temperature was recorded throughout FD to estimate circadian period and phase, and lipid data were averaged across 4h circadian phase bins. Results: Plasma triglyceride levels varied by circadian phase (p<0.0001), as did the ratio for triglycerides/total cholesterol and triglycerides/HDL (p<0.0001). All were highest at circadian phase 0° (late biological night, 1-2h before usual waketime), and lowest at phase 180 (biological day). Depending on the diet, the range in triclycerides was 15-25mg/dL. In this small sample we did not find a significant rhythm in cholesterol, HDL, LDL, or VLDL. There was a significant effect of diet on triglyceride levels (p=0.0270) but not other lipids. Conclusion: The plasma triglyceride/HDL cholesterol ratio, which predicts insulin resistance and the incidence of coronary artery disease, is highest during the late biological night. Our results therefore have implications for routine clinical testing of lipids, where the time of day at which the sample is taken relative to the patient's internal rhythms should be considered when interpreting the results. Support (If Any): Study supported by P01AG009975 and conducted in the Brigham and Women's Hospital Center for Clinical Investigation, part of Harvard Clinical and Translational Science Center supported by UL1TR001102. RKY supported by T32HL007901 and F32HL143893. NV supported by T32HL007901 and F32AG051325.